2018
DOI: 10.1113/jp276467
|View full text |Cite
|
Sign up to set email alerts
|

Glycinergic neurotransmission in the rostral ventrolateral medulla controls the time course of baroreflex‐mediated sympathoinhibition

Abstract: Key points To maintain appropriate blood flow to various tissues of the body under a variety of physiological states, autonomic nervous system reflexes regulate regional sympathetic nerve activity and arterial blood pressure. Our data obtained in anaesthetized rats revealed that glycine released in the rostral ventrolateral medulla (RVLM) plays a critical role in maintaining arterial baroreflex sympathoinhibition. Manipulation of brainstem nuclei with known inputs to the RVLM (nucleus tractus solitarius and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
(138 reference statements)
1
6
0
Order By: Relevance
“…The finding in the present study that systolic and diastolic blood pressure decreased after 4 to 8 weeks' administration of glycine may be related to the peripheral vasodilation caused by binding of glycine to N-methyl-D-aspartate receptors in the suprachiasmatic nucleus shell [18]. Glycine also binds to these receptors in the rostral ventral medulla, an area involved in the maintenance of arterial baroreceptor reflex [19]. Furthermore, a study in rats with diabetes showed that oral glycine leads to an increase in blood nitric oxide levels, resulting in vasodilation [20].…”
Section: Discussionsupporting
confidence: 50%
“…The finding in the present study that systolic and diastolic blood pressure decreased after 4 to 8 weeks' administration of glycine may be related to the peripheral vasodilation caused by binding of glycine to N-methyl-D-aspartate receptors in the suprachiasmatic nucleus shell [18]. Glycine also binds to these receptors in the rostral ventral medulla, an area involved in the maintenance of arterial baroreceptor reflex [19]. Furthermore, a study in rats with diabetes showed that oral glycine leads to an increase in blood nitric oxide levels, resulting in vasodilation [20].…”
Section: Discussionsupporting
confidence: 50%
“…Inhibition of nTS neuronal activity produced a large, sustained increase in SSNA, likely due at least in part to blockade of arterial baroreflex function and the prolonged effects of muscimol ( Gao et al, 2019 ). Exposure to AIH had no additional effect on the level of SSNA; elevated SSNA after nTS muscimol was similar in animals subsequently exposed to either TC or AIH.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we sought to identify the non‐catecholaminergic VLM neurons targeted by the vmPFC. Prior work has demonstrated that a local network of inhibitory neurons acts on VLM catecholaminergic neurons to regulate sympathoexcitation (Gao et al., 2019; Guyenet et al., 1990; Heesch et al., 2006). In fact, GABAergic and glycinergic neurons are recruited by barosensitive‐neurons in the nucleus of the solitary tract to regulate RVLM outflow and control blood pressure (Guyenet, 2006; Schreihofer & Guyenet, 2002).…”
Section: Resultsmentioning
confidence: 99%